Eltrombopag for the treatment of children with persistent and chronic immune thrombocytopenia (PETIT): a randomised, multicentre, placebo-controlled study. Issue 8 (August 2015) - Bussel, James B; de Miguel, Purificación Garcia; Despotovic, Jenny M; Grainger, John D; Sevilla, Julián; Blanchette, Victor S; Krishnamurti, Lakshmanan; Connor, Philip; David, Michèle; Boayue, Koh B; Matthews, Dana C; Lambert, Michele P; et al.
Summary: Background: The oral thrombopoietin receptor agonist eltrombopag is approved for treatment of adults with chronic immune thrombocytopenia. In the PETIT trial, we aimed to investigate the efficacy and safety of eltrombopag in children with persistent or chronic immune thrombocytopenia. Methods: PETIT was a three-part, randomised, multicentre, placebo-controlled study done at 22 centres in the USA, UK, Canada, Spain, France, and the Netherlands. Patients aged 1–17 years with immune thrombocytopenia lasting for 6 months or longer and platelets less than 30 × 10 9 per L who had received at least one previous treatment were enrolled. We enrolled patients into three cohorts consisting of patients aged 12–17, 6–11, and 1–5 years. We established patients' starting doses with an open-label, dose-finding phase with five patients in each cohort. During the dose-finding phase, patients aged 6–17 years started eltrombopag at 25 mg once per day (12·5 mg for those weighing <27 kg) and patients aged 1–5 years received 0·7 mg/kg per day to a maximum of 2 mg/kg unless otherwise approved. We permitted dose adjustments on the basis of platelet response up to a maximum dosage of 75 mg per day. Additional patients were then recruited and randomly assigned (2:1) to receive either eltrombopag or placebo tablets (or oral suspension formulation if aged 1–5 years) once per day for 7 weeks at the previously established doses. Starting doses for the double-blind phase were 37·5 mg/day for patients aged 12–17 years; 50 mg/day for patients weighing 27 kg or more (25 mg for east Asian patients) and 25 mg/day for patients weighing less than 27 kg (12·5 mg once per day for east Asian patients) for patients aged 6–11 years; and 1·5 mg/kg once per day (0·8 mg/kg once per day for east Asian patients) for patients aged 1–5 years. Randomisation was done by the GlaxoSmithKline Registration/Medication Ordering System and both patients and study personnel were masked to treatment assignments. Patients who completed treatment were then enrolled into an open-label phase and all patients could receive up to 24 weeks of eltrombopag. The primary outcome was the proportion of patients achieving a platelet count of 50 × 10 9 per L or more at least once from weeks 1–6 (days 8 to 43) of the randomised phase of the study in the absence of rescue therapy. We assessed efficacy in the intent-to-treat population, which consisted of all patients assigned to treatment, and we assessed safety in all patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT00908037 . Findings: Between Oct 2, 2009, and June 22, 2011, we recruited 15 patients, with five patients in each age cohort, into the open-label dose-finding phase who did not progress into the double-blind phase. From March 17, 2010, to Jan 15, 2013, we randomly assigned 67 patients to treatment, with 45 patients assigned to receive eltrombopag (16 children aged 12–17 years, 19 aged 6–11 years, and ten aged 1–5 years) and 22 to receive placebo (eight children aged 12–17 years, nine aged 6–11 years, and five aged 1–5 years). However, two patients assigned to receive eltrombopag did not receive the study drug and one was lost to follow-up, and one patient assigned to receive placebo was given eltrombopag. From weeks 1 to 6, 28 (62%) patients who received eltrombopag, compared with seven (32%) who received placebo, achieved the primary endpoint of platelet count 50 × 10 9 per L or more at least once without rescue (odds ratio 4·31, 95% CI 1·39–13·34, p=0·011). The most common adverse events with eltrombopag were headache (13 [30%] patients receiving eltrombopag vs nine [43%] patients receiving placebo), upper respiratory tract infection (11 [25%] patients vs two [10%] patients), and diarrhoea (seven [16%] patients vs one [5%] patient). Grade 3 or 4 adverse events occurred in five (11%) patients receiving eltrombopag and four (19%) patients receiving placebo, and serious adverse events (four [9%] patients receiving eltrombopag and two (10%) patients receiving placebo) were similarly infrequent in both groups. No thrombotic events or malignancies occurred. Increased alanine aminotransferase concentrations caused two (3%) of 65 patients to discontinue eltrombopag in the open-label phase. Interpretation: Our results showed that eltrombopag could be used to increase platelet counts and reduce clinically significant bleeding in children with persistent or chronic immune thrombocytopenia. Prevalence of increased liver laboratory values was similar to that seen in adults. Funding: GlaxoSmithKline.